2022
DOI: 10.3390/catal12080829
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of a Titanium Dioxide Additivated Thermoset

Abstract: The transmission of pathogens via surfaces poses a major health problem, particularly in hospital environments. Antimicrobial surfaces can interrupt the path of spread, while photocatalytically active titanium dioxide (TiO2) nanoparticles have emerged as an additive for creating antimicrobial materials. Irradiation of such particles with ultraviolet (UV) light leads to the formation of reactive oxygen species that can inactivate bacteria. The aim of this research was to incorporate TiO2 nanoparticles into a ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…However, the synthesis of TiO 2 -graphene composite structures can often involve high temperatures, high pressures, or toxic reagents, necessitating further investigation to discover simpler methods of preparation for dental applications [4]. Titanium dioxide has well-established antimicrobial properties when exposed to ultraviolet light and generates bactericidal species through photolysis reactions [5]. It is suggested that the photocatalytic killing mechanism is sequential, rst causing damage to the bacterial surface components, then degrading the cell membrane, and nally causing leakage of intracellular components from the cytoplasm resulting in cell death [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the synthesis of TiO 2 -graphene composite structures can often involve high temperatures, high pressures, or toxic reagents, necessitating further investigation to discover simpler methods of preparation for dental applications [4]. Titanium dioxide has well-established antimicrobial properties when exposed to ultraviolet light and generates bactericidal species through photolysis reactions [5]. It is suggested that the photocatalytic killing mechanism is sequential, rst causing damage to the bacterial surface components, then degrading the cell membrane, and nally causing leakage of intracellular components from the cytoplasm resulting in cell death [6].…”
Section: Introductionmentioning
confidence: 99%